2015
DOI: 10.1111/jfr3.12143
|View full text |Cite
|
Sign up to set email alerts
|

Application of multi‐objective evolutionary algorithms for the rehabilitation of storm sewer pipe networks

Abstract: In recent decades, evolutionary optimisation algorithms have been used successfully for a wide variety of water resources engineering problems and their applications are still increasing. In this research work, a hybrid harmony search algorithm, "Non-dominated Sorting Harmony Search" algorithm (NSHS) is developed and compared with two state of the art multi-objective evolutionary algorithms -the NSGA-II and MOPSO algorithms -for assigning optimal rehabilitation plans for sewer pipe networks. The algorithms con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…However, methods based on the concept of return period do not take into account economic issues. It might result in both overdesigned or underdesigned networks [20]. Cost-optimal design of hydraulic network is a complex problem for engineers.…”
Section: Applicationmentioning
confidence: 99%
“…However, methods based on the concept of return period do not take into account economic issues. It might result in both overdesigned or underdesigned networks [20]. Cost-optimal design of hydraulic network is a complex problem for engineers.…”
Section: Applicationmentioning
confidence: 99%
“…Several applications of this algorithm have been reported in the water engineering literature and a few multi-objective schemes have recently been developed [27,30] combining HS operators with non-domination sorting (NS) and crowding distance criteria to generate Pareto-optimal solutions in multi-objective problems. This algorithm called NSHS was compared with the NSGA2 and MOPSO algorithms based on several benchmark problems and a sewer pipe network application and the results showed that the NSHS algorithm outperformed the other two.…”
Section: Non-dominated Sorting Harmony Search (Nshs) Algorithmmentioning
confidence: 99%
“…It is expected that if this method is combined with a local search optimizer, the performance of the evolutionary search improves. According to a study by Yazdi et al [27], the harmony search performs very well in finding optimal solutions located in certain parts of the search space, but cannot generate adequately diverse Pareto-optimal solutions, thus degrading the overall performance of the search algorithm. To exploit the local search advantages of HS and the exploratory strength of DE, we propose a hybrid HS-DE method here.…”
Section: Proposed Algorithm Non-dominated Sorting Harmony Search Difmentioning
confidence: 99%
See 1 more Smart Citation
“…By searching over a large set of feasible solutions, metaheuristics can often find good solutions with less computational effort [2]. There has been a widespread usage of metaheuristics and their applications in artificial intelligence, e.g., transit network design problems [3], sewer pipe networks [4], water distribution systems [5], sizing optimization of truss structures [6], ordinary differential equations [7], and so forth. Using metaheuristic algorithms, complex problems are not far from finding their solutions [7].…”
Section: Introductionmentioning
confidence: 99%